The quality of financial advice: What influences recommendations to clients? - d’Astous, Philippe; Gemmo, Irina; Michaud, Pierre-Carl (Journal of Banking & Finance, 2024)
In this paper, we conduct a field experiment with a large sample of financial planner professionals in Canada to elicit factors which may influence client recommendations. Using repeated client vignettes, we find that recommendations are sensitive in expected ways to relative costs and benefits of particular products as well as client characteristics. We show that, in some domains, planners are more likely to recommend products they own themselves, their spouse owns, or they are licensed to sell. We provide evidence that product familiarity can negatively impact the quality of financial advice in specific situations. Finally, we find evidence for an effect of client involvement in the investment domain, but we do not find economically significant gender effects.